The determinants of dividend policy in Ghana: evidence from the Ghana stock exchange. - ANANE, ESTHER (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partial Fulfilment Of The Requirements For The Degree Of Master In Business Administration (Accounting)